Characteristics of Open Globe Injuries in Preschool Children. Issue 10 (October 2015) - Gunes, Alime; Kalaycı, Mustafa; Genc, Oğuzhan; Ozerturk, Yusuf
Abstract : Purpose: To evaluate the demographic, etiologic, and clinical characteristics of open globe injuries in preschool children. Methods: The medical files of preschool children who had an operation for an open globe injury from January 2003 to January 2013 were retrospectively analyzed. The patients' demographics and injury characteristics were recorded. Results: The study consisted of 44 preschool children with an open globe injury. The mean age was 4.38 ± 1.39 years. Most of the injuries occurred in boys (32/44). All patients were followed up for at least 3 months (mean, 8.47 ± 6.38 months; range, 3–24 months). The mean time between injury and operation was 10.40 ± 5.94 hours. Injuries happened most frequently at home (45.4%), and the most common cause of injury was kitchen items (25%). The final visual acuity could be evaluated only in 21 patients, and 90.4% of them had residual vision deficit. Conclusions: Because open globe injuries occur most frequently at home or in the immediate surroundings of the house, higher awareness of parents and child care providers is extremely important to prevent these injuries in preschool children.